The 2006-2007 Rift Valley fever outbreak in Kenya: Sources of early warning messages and response measures implemented by the Department of Veterinary Services - Gachohi, John M.; Bett, Bernard K.; Njogu, G.; Mariner, Jeffrey C.; Jost, Christine (2012)
The authors characterised sources of early warning messages about occurrences of Rift Valley fever (RVF) and examined the response measures that were used by the Department of Veterinary Services (DVS) to manage the 2006–2007 RVF outbreaks in Kenya. The study was conducted between November 2009 and March 2010 and it included national, provincial and district veterinary officers who were involved in the management of the outbreak. Structured questionnaires were used to collect the data. Although the majority of the respondents reported having limited capacity to implement response measures, they perceived that the measures implemented were effective. Vaccination, movement control and market closures were the main response measures implemented, particularly in districts that had cases in both livestock and humans. Vaccination, however, was implemented too late and the coverage achieved was too low to be effective. The authors suggest ways to improve the capacity of the DVS to respond to similar outbreaks in the future.